ESTRESSE EM MÃES DE CRIANÇAS COM A SÍNDROME CONGÊNITA DE ZIKA (Movimenta (ISSN 1984-4298), 2021)
Objective: to evaluate stress symptoms in mothers of children with Congenital Zika Syndrome (CZS) and to verify whether manifestations of stress are associated with socioeconomic and clinical variables. Method: this descriptive cross-sectional study was carried out in a rehabilitation center located in Goiânia/Goiás, Brazil. The sample included mothers of children with CZS. The collection instruments were questionnaire of clinical data of the children and mothers, sociodemographic questionnaire, Lipp Stress Symptoms Inventory for Adults (LSSI). Results:  Participants were 30 mothers of children with CZS, with a mean age of 30.57 years. The children's mean age was 2.4 years and their mean head circumference was 28.7 centimeters. Regarding the assessment of maternal stress, 66.7% of the mothers presented symptoms of stress, 80.0% were in the resistance phase and psychological symptoms predominated (55.0%). Manifestations of symptoms of maternal stress were not associated with variables of the sociodemographic and clinical profile. Conclusion: the mothers were in the process of psychological illness. The study highlights the importance of providing an in-depth assessment and referral for psychological treatment and support, in order for these mothers to cope with the high demands.Keywords: Psychological stress Mothers. Congenital Zika Syndrome. Microcephaly. Zika virus.